A new ESIPT-based fluorescent probe for the highly sensitive detection of amine vapors. (28th May 2021) - Bao, Cheng; Shao, Sufang; Zhou, Haifeng; Han, Yifeng
Abstract : A new ESIPT-based fluorescent probe has been developed as a rapid, highly sensitive, and selective sensor for amine vapors. Abstract : Volatile amine vapors are toxic and corrosive irritants and can cause serious health problems. In addition, the biologically amine vapor produced by microorganisms is also an important indicator of food spoilage. Therefore, the development of simple, sensitive, and selective amine vapor detection methods is of great significance. A new ESIPT-based fluorescent probe HBTAc has been developed as a rapid, highly sensitive, and selective sensor for amine vapors in this work. The HBTAc sensor exhibits an obvious fluorescence turn-on response at 514 nm toward amine vapors with a large Stokes shift (180 nm), and a low detection limit (12.7 ppm). Taking advantage of its portability and high sensitivity to amine vapors, the HBTAc sensor can be used for food spoilage monitoring by detecting volatile amines produced by microbial growth. Finally, agar gels based on the HBTAc probe were fabricated, which could act as a solid optical sensor to conveniently and efficiently detect amine vapors.